Examining “privatization” and protecting equal rights - Berner, Ashley (Frontiers in Education, 2025)
This opinion piece examines, and resists, the term “privatization” in characterizing non-state participation in national and provincial school systems. First, since the late 18th century, modern governments have often relied on civil society to deliver public education, and on private industry to create the “goods” that make public education possible (from textbooks and chalkboards to wireless networks and data systems). Second, the presence of non-state actors in education can work either for or against equality of access and equality of excellence. It depends on (1) the fairness of the enabling processes; (2) transparent accountability systems; (3) equity-oriented regulations, especially around admissions policies; and (4) full funding by governments, with support calibrated to students' specific and variable needs. Third, “privatization” derives from U.S.-centric debates that depend on unhelpful binaries. We need better ways to describe the participation of non-state actors that reflect historical realities and universal rather than particularist concerns.